2019
DOI: 10.15171/jlms.2019.51
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Effects of Transcranial Near-Infrared Photobiomodulation on Motor Performance in Healthy Human Subjects: An Experimental SingleBlind Randomized Clinical Trial

Abstract: Introduction: Transcranial near-infrared photobiomodulation (NIR-PBM) is a new noninvasive procedure which transcranially applies a near-infrared wavelength to the scalp with a laser or a light-emitting diode (LED) source. Improvement in the neurological or psychological symptoms has been reported following light irradiation. However, to our knowledge, there is no study to investigate the effects of transcranial NIR-PBM on motor performance directly. Therefore, the objective of this study was to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
9
0
2
Order By: Relevance
“…In the context of non-invasive brain stimulation approaches, a growing number of studies are investigating the effects of low power red to near infrared coherent lights on the brain functions [1][2][3][4][5][6][7][8][9][10][11]. This method has been known as photobiomodulation (PBM) and various studies have applied that as intracranial [12,13] and intranasal [3,8] brain stimulation approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of non-invasive brain stimulation approaches, a growing number of studies are investigating the effects of low power red to near infrared coherent lights on the brain functions [1][2][3][4][5][6][7][8][9][10][11]. This method has been known as photobiomodulation (PBM) and various studies have applied that as intracranial [12,13] and intranasal [3,8] brain stimulation approaches.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been known as photobiomodulation (PBM) and various studies have applied that as intracranial [12,13] and intranasal [3,8] brain stimulation approaches. However, a group of studies suggested the applicability of the PBM as a transcranial brain stimulation technique for cognitive and behavioral improvements in health and diseases [5,[7][8][9]. Transcranial PBM (tPBM) emits converge light to one or several specific regions of scalp and modulates brain activity via the transferred light energy to the neural cells [3,5,9,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…The single session of transcranial laser therapy [infrared (808 nm), continuous wave, (5 min, 60 J/cm 2 , and 200 mW/cm 2 ) applied on skull (C3 point—located on the left primary motor cortex)] in healthy subjects showed an increase in the number of finger taps in bilateral upper extremities, indicating improvement of the motor control and performance [38]. In addition, the application of transcranial laser may have potentiated the exercise induced by NMES in the paretic upper limb (wrist extension), resulting in the enhanced manual dexterity due to systemic effects of photobiomodulation.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy young adults, the right PFC tPBM has been shown to improve memory and attention [40,42]. In the study by Fekri et al (2019), motor performance improved following tPBM [43]. Some electroencephalographic studies have reported changes in absolute power and functional connectivity of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Fekri et al . (2019), motor performance improved following tPBM [ 43 ]. Some electroencephalographic studies have reported changes in absolute power and functional connectivity of the brain.…”
Section: Discussionmentioning
confidence: 99%